Implementasi Metode RAD Dalam Pengembangan Sistem Informasi Stok Barang Dengan Srategi FEFO Berbasis Web - Ahmad Mulyana; Irsan Jaelani; Bayu Prasetio (Jurnal Teknologika, 2025)
Toko Sembako Mulia has adopted a web-based system to track the movement of inventory, including incoming and outgoing goods. Despite this, reports on sales, purchases, and stock-taking are still recorded manually, which increases the risk of data inconsistencies—especially when managing expired items. To overcome this challenge, an inventory management system was developed using the First Expired First Out (FEFO) strategy, the Rapid Application Development (RAD) method, and design modeling with Unified Modeling Language (UML). The system was implemented using the CodeIgniter framework, PHP as the programming language, and MySQL for database management. The resulting system provides features for managing stock reports, purchase and sales transactions, as well as employee and supplier information